PENGEMBANGAN INSTRUMEN TES KEMAMPUAN BERPIKIR TINGKAT TINGGI MATERI FLUIDA DAN GETARAN HARMONIS - Akhsan, Hamdi; Wiyono, Ketang; Novianti, Rizki; Melvany, Nanda Eva; Ariska, Melly (Jurnal Inovasi Pendidikan, 2019)
, This research aims to produce a valid and reliable higher order thinking skills (HOTS) physics test instrument of high school. This research took place in the even semester of school year 2018/ 2019 at Physics Education Student FKIP Universitas Sriwijaya. In this study, researchers used a 4D development model implemented of 4 stages: define, design, development and disseminate, but on this researchers only limited to the stage of development. In the development phase consists of several steps; expert appraisal, limited trials, and large-scale trials. The results of this indicate (1) the instruments validation test in an expert appraisal (expert judgement) was assessed by two expert to assess the construct, content and empirical aspects of Prototype I that had been made by providing walktrough assessment sheets along with comments and suggestions with an average of validity score was 89% with a very valid category; (2) reliable testing of instruments assessed from development testing at the stage of field testing found that the average reliability score of the trial phase was limited and large-scale trials in sequence were 0,76 and 0,67 with high levels of reliability. Thus, based on the results of the research data, it was found that higher order thinking skills (HOTS) physics test instrument on Fluid and harmonic vibrations of high school developed was classified as valid and reliable.